Peran Kepemimpinan Komunikasi Internal dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan Pada Perusahaan Telekomunikasi - Anshori, M Isa; Caroline; Putro, Suryati Eko; Ariyadi, Muhammad Yusuf (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research is an empirical study which aims to analyze the impact of leadership, internal communication, and career development on employee job satisfaction at Plasa Telkom East Java and Central Java Province. The research was conducted at the Plaza offices of East Java and Central Java Province involving the employee population (93 respondents) and using questionnaires and documentation as data collection tools. The research results show that partially, leadership and internal communication have a significant impact on employee job satisfaction, while career development does not show a significant impact. Overall, these three variables have a significant impact on the job satisfaction of Plasa Telkom employees in East Java and Central Java Province, with leadership as the most dominant factor, indicated by a regression coefficient value that is greater than the smallest probability value. The relationship between leadership, internal communication, career development and employee job satisfaction show a positive and significant correlation. However, the role of these three variables in supporting employee job satisfaction is still relatively less dominant, which may indicate that there are other factors outside the research framework that have a greater contribution to employee job satisfaction.